Retracted:DETERMINAN YANG MEMPENGARUHI JUMLAH KREDIT PEMILIKAN RUMAH (KPR) DI PROVINSI NTB TAHUN 2012-2019 - N Nurraahmania; Rifki Khoirudin (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2022)
RETRACTEDFollowing a rigorous and careful concerns and consideration in the review of the article published in Jurnal Equilbrium: Jurnal Ilmiah Ekonomi dan Pembelajaranya entitled “DETERMINAN YANG MEMPENGARUHI JUMLAH KREDIT PEMILIKAN RUMAH (KPR) DI PROVINSI NTB TAHUN 2012-2019” Vol 10, No 2, pp. 164-171, Juli 2022, DOI: 10.25273/equilibrium.v10i2.8075This paper has been found to violate the principles of Jurnal Equilibrium: Jurnal Ilmiah Ekonomi dan Pembelajaranya and has been retracted.The article has contained redundant material and throughout a careful examination, the editor has found that the paper has also been published in Journal Economics Technology and Enterpreneur Vol 1 No 1, page 20-28, Maret 2022.The document and its content have been removed from Jurnal Equilibrium: Jurnal ilmiah Ekonomi dan Pembelajaranya, and reasonable effort should be made to remove all references to this article.Permalink/ DOI: 10.25273/equilibrium.v10i2.8075